Clinical Features and Genetic Analysis of 48 Patients with Chronic Granulomatous Disease in a Single Center Study from Shanghai, China (2005–2015): New Studies and a Literature Review - Jing Wu; Wei-Fan Wang; Yi-Dan Zhang; Tong-Xin Chen (Journal of Immunology Research)
Chronic Granulomatous Disease (CGD) is a rare inherited primary immunodeficiency, which is characterized by recurrent infections due to defective phagocyte NADPH oxidase enzyme. Nowadays, little is known about Chinese CGD patients. Here we report 48 CGD patients in our single center study, which is the largest cohort study from Mainland China. The ratio of male to female was 11 : 1. The mean onset age was 0.29 years old, and 52% patients had an onset within the 1st month of life. The mean diagnosis age was 2.24 years old. 11 patients (23%) had died with an average age of 2.91 years old. 13 patients (28%) had positive family histories. The most prevalent infectious sites were the lungs (77%), followed by gastrointestinal tract (54%), lymph nodes (50%), and skin (46%). In addition, septicopyemia, thrush, and hepatosplenomegaly were also commonly observed, accounting for 23%, 23%, and 40% of the cases. Lesions due to BCG vaccination occurred in more than half of the patients. X-linked CGD due to CYBB gene mutations accounted for 75% of the cases, and 11 of them were novel mutations. Autosomal recessive inheritance accounted for 6% patients, including 1 patient with CYBA, 1 with NCF1, and 1 with NCF2 gene mutations.